INEQUALITY AND EXTREME POVERTY IN MAYAN INDIGENOUS WOMEN IN QUINTANA ROO, MEXICO - Barrera-Rojas, Miguel Angel (2019)
This work presents research results about the conditions of poverty that arise in the Maya area of Quintana Roo, Mexico, particularly in women. For the methodological development, the variable Current Income of the National Household Income and Expenditure Survey in Mexico was replicated, field work was carried out in localities oftwo municipalities in the Maya area of Quintana Roo, Mexico and the data collected werecontrasted against three indicators of poverty: extreme poverty line proposed by the World Bank, and the minimum well-being line and welfare line proposed by the National Council for the Evaluation of Social Development Policy. Finally, results are presented where it is evident that, in fact, there are conditions of extreme poverty in the population under study and that women have incomes far below and unequal to what men have, this, coupled with the fact that income of women are supported mainly by money from programs to combat poverty.